2020
DOI: 10.9734/ajahr/2020/v5i330052
|View full text |Cite
|
Sign up to set email alerts
|

Sowing Dates and Fertilizer Application on Growth and Yield of Muskmelon (Cucumis melo L.) at Ado-Ekiti

Abstract: Information on some agronomic practices are required for muskmelon production as there is no record of its production in Ado-Ekiti. A field study of 3 x 2 factorial experiment of sowing dates (January, May and September) and NPK 15:15:15 fertilizer application (0 and 333 kg ha -1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…The other treatments fell within the range between these two values. Similar findings were also reported by Matthew [6] in muskmelon, where they observed that the application of inorganic fertilizers along with organic manures increased the number of leaves per plant.…”
Section: Average Number Of Leaves Per Plantsupporting
confidence: 88%
See 1 more Smart Citation
“…The other treatments fell within the range between these two values. Similar findings were also reported by Matthew [6] in muskmelon, where they observed that the application of inorganic fertilizers along with organic manures increased the number of leaves per plant.…”
Section: Average Number Of Leaves Per Plantsupporting
confidence: 88%
“…In 2019, Matthew [6] conducted a study in the African country of Nigeria to investigate the effects of sowing dates and nutrients application on the growth and yield of muskmelon. He found that the sowing dates did not significantly influence overall growth, but muskmelons planted in May exhibited a higher number of leaves per plant, increased leaf area, and longer vine length.…”
Section: Introductionmentioning
confidence: 99%